SAT0478 Effect of Complete Spinal Cord Injury on Bone Turnover and Bone Mineral Density (BMD) Evolution. A One Year Follow-Up Study. (10th June 2014) - Gifre, L.; Vidal, J.; Portell, E.; Monegal, A.; Muxi, A.; Guañabens, N.; Peris, P.
Abstract : Background: Spinal cord injury (SCI) has been associated with marked bone loss and an increased risk of fractures under the SCI level. Objectives: To analyze the effect of recent complete SCI on bone turnover and BMD evolution and factors related to bone loss. Methods: Prospective study including patients with complete motor SCI (ASIA A or B) (<6 months). Bone turnover markers (bone formation: P1NP, bone ALP; resorption: sCTx) and BMD (lumbar spine and femur (DXA)) were assessed in all patients at baseline and at 6 and 12 months. Risk factors for osteoporosis, SCI level (paraplegia/tetraplegia), lesion type (spastic/flaccid), SCI severity (ASIA score) and fractures were evaluated, comparing results with a control group. Results: 42 patients (40M:2F) (mean age 35±14years) were included 100±33days after SCI (ASIA A 39:B 3). 55% had paraplegia and 78% spasticity. 24 were followed-up at 6 months and 22 at 12 months. Compared to controls, bone turnover markers were markedly increased just after SCI (P1NP:194±124 vs. 50±19ng/ml, p<0.001; bone ALP:15±7 vs. 12±4ng/ml, p=0.04; sCTx1.48±0.52 vs. 0.49±0.23ng/ml, p<0.001), with maintained, although with less increased, values at 6 and 12 months. BMD decreased progressively at proximal femur (-13±5% at 6months, p<0.001; -20±8% at 12months, p<0.001), with no significant changes at lumbar BMD. At 12 months 59% of the SCI patients presented densitometric osteoporosis. Patients with higher sCTX values after SCI (3rd tertile) had the highest femur BMD loss at 12 months (-23%). No relationship was observed between BMD and bone marker changes, or SCI level or lesion type. Conclusions: Patients with complete SCI have increased bone turnover after injury with marked bone loss under the injury level of ∼-20% of BMD at the proximal femur at one year, being more marked in individuals with the highest sCTX levels. Awareness of this complication and its therapeutic approach are mandatory. Acknowledgements: Work funded by a grant from Fundaciό La Maratό de TV3. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5116